Comprehensive comparison and experimental validation of band-structure calculation methods in III–V semiconductor quantum wells. (January 2016) - Zerveas, George; Caruso, Enrico; Baccarani, Giorgio; Czornomaz, Lukas; Daix, Nicolas; Esseni, David; Gnani, Elena; Gnudi, Antonio; Grassi, Roberto; Luisier, Mathieu; Markussen, Troels; Osgnach, Patrik; et al.
Abstract: We present and thoroughly compare band-structures computed with density functional theory, tight-binding, k · p and non-parabolic effective mass models. Parameter sets for the non-parabolic Γ, the L and X valleys and intervalley bandgaps are extracted for bulk InAs, GaAs and InGaAs. We then consider quantum-wells with thickness ranging from 3 nm to 10 nm and the bandgap dependence on film thickness is compared with experiments for In 0.53 Ga 0.47 As quantum-wells. The impact of the band-structure on the drain current of nanoscale MOSFETs is simulated with ballistic transport models, the results provide a rigorous assessment of III–V semiconductor band structure calculation methods and calibrated band parameters for device simulations.